GRADASI PEMBUNUHAN DALAM TRADISI COMMON LAW DAN CIVIL LAW: MENS REA, PEMBELAAN PARSIAL, DAN PROPORSIONALITAS - Zul Khaidir Kadir (CV. ADIBA AISHA AMIRA, 2026)
This article examines how different legal traditions construct degrees of liability in homicide through the relationship between mens rea, culpability, legal grade, and punishment. It focuses on the distinction between murder and manslaughter, and on how provocation, diminished responsibility, recklessness, felony murder, and constructive murder shape the boundaries between homicide grades. The study employs doctrinal-comparative analysis and functional comparison by examining common law and civil law traditions through selected illustrative jurisdictions, namely England and Wales, the United States, Canada, Australia, Germany, and France. The findings show that the central problem in homicide grading lies in the instability between degree of fault, legal label, and penal consequence. Partial defences may prevent murder from operating too rigidly, yet they may also produce under-labelling when mitigation is overly broad or excessively offender-centred. Conversely, felony murder, constructive murder, and extreme recklessness may generate over-labelling when the fatal result or the context of the underlying offence substitutes for a specific assessment of the defendant’s mental state toward death. The article implies that a proportionate homicide system must punish lethal violence seriously while preserving meaningful distinctions between levels of culpability.